2020
DOI: 10.1126/sciadv.aba9950
|View full text |Cite
|
Sign up to set email alerts
|

A novel cardiomyogenic role for Isl1 + neural crest cells in the inflow tract

Abstract: The degree to which populations of cardiac progenitors (CPCs) persist in the postnatal heart remains a controversial issue in cardiobiology. To address this question, we conducted a spatiotemporally resolved analysis of CPC deployment dynamics, tracking cells expressing the pan-CPC gene Isl1. Most CPCs undergo programmed silencing during early cardiogenesis through proteasome-mediated and PRC2 (Polycomb group repressive complex 2)–mediated Isl1 repression, selectively in the outflow tract. A notable exception … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The subendocardial location of cycling cardiomyocyte may indicate their origin of a subset of cardiac progenitors derived from the second heart field 38 or cardiac neural crest cells (CNCs). Recent studies reported that CNCs generate a number of trabecular cardiomyocytes that undergo multiple clonal division during compaction, and also continue to generate cardiomyocytes after birth, suggesting that postnatal heart sustains cardiomyocyte-producing CNCs 39 . Others have suggested that differential oxygen levels in the subendocardium vs. the outer ventricular layer may enhance cardiomyocyte cell cycle activity 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The subendocardial location of cycling cardiomyocyte may indicate their origin of a subset of cardiac progenitors derived from the second heart field 38 or cardiac neural crest cells (CNCs). Recent studies reported that CNCs generate a number of trabecular cardiomyocytes that undergo multiple clonal division during compaction, and also continue to generate cardiomyocytes after birth, suggesting that postnatal heart sustains cardiomyocyte-producing CNCs 39 . Others have suggested that differential oxygen levels in the subendocardium vs. the outer ventricular layer may enhance cardiomyocyte cell cycle activity 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Since BMP inhibition ( Sun et al., 2015 ), as well as p38 inhibition and Isl1 depletion, resulted in decreased expression of the SAN lineage markers Hcn4 and Shox2 and decreased heart rate, and TAK1 activates p38 MAPK, it remains to be determined whether the BMP-TAK1-p38-ISL1 axis and ISL1 phosphorylation control the differentiation toward the SAN lineage. Interestingly, a recent study has shown that ISL1 is degraded through the ubiquitin-proteasome pathway selectively in the OFT but not in the SAN and the inflow tract region of postnatal hearts, raising the question whether the above-described mechanism is required for ISL1 protein stabilization in the SAN ( Hatzistergos et al., 2020 ). On the other hand, BMP-SMAD signaling directly suppresses Isl1 expression through miRNA17 and miRNA20a ( Wang et al., 2010 ), ensuring proper differentiation of working myocardial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The SHF is patterned into anterior (aSHF) and posterior (pSHF) domains along the arterial and venous poles of the FHF-derived linear heart tube, respectively (Hatzistergos et al 2020). Both domains are kept in a proliferative progenitor cell state for several days as they become the main resource for the new CMs needed for the elongation of the heart tube and subsequent development of the right ventricle (RV) and atria.…”
Section: Early Development Of Cardiomyocytesmentioning
confidence: 99%
“…In the aSHF, this is achieved partly through synergism between Wnt/β-catenin and Fgf10 signaling, which are maintained active by Isl1 and Tbx1, whereas the pSHF is maintained through Wnt/β-catenin and RAmediated activation of Hox genes (Bertrand et al 2011). Notably, in aSHF and pSHF cardioblasts Isl1 is activated through distinct cis-regulatory elements (Hatzistergos et al 2020). In addition, the aSHF is regulated through oxygen tension (Yuan et al 2017).…”
Section: Early Development Of Cardiomyocytesmentioning
confidence: 99%